PENCEGAHAN KEJADIAN TUBERKULOSIS PARU BTA POSITIF - Vivick Artha R S; Nur Haidah; Narwati . (GEMA LINGKUNGAN KESEHATAN, 2019)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which spreads through droplet nuclei. Pulmonary tuberculosis can cause death if it is not treated, so efforts need to be made to eradicate pulmonary tuberculosis. One of the effort to eradicate some cases of pulmonary tuberculosis is to improve health behavior by preventing bad behavior. Behavior is the implementation of knowledge, attitudes and actions. The purpose of this research is to determine the relationship of preventive behavior to the incidence of positive BTA pulmonary.This study uses a simple random sampling method with a case control study approach. The population was random patients with positive BTA pulmonary TBC as a case of 59 respondents and neighbors of patients who did not suffer from pulmonary TBC as a control 59 respondents with a total of 118 respondents. Data collection is done by interviewing with questionnaires.The results showed that there was a relationship between knowledge (p-value = 0.006 0.05) with the incidence of Positive AFB Tuberculosis. There was no relationship between attitudes (p-value = 0.580 0.05) with the incidence of Positive BTA Tuberculosis. There is a relationship between precautionary measures (p-value = 0.001 0.05) on the incidence of Positive BTA Tuberculosis in the Work Area of Manukan Kulon Health Center.It was concluded that there was no between attitudes towards the incidence of Positive BTA, but there was a relationship between knowledge and preventive measures for the incidence of Positive BTA Tuberculosis. It is recommended to health service providers who have built Pulmonary TBC cadres to increase pulmonary TBC eradication activities to reduce the number of Lung Tuberculosis cases in the Manukan Kulon Health Center Work Area by visiting each BTA patient and their neighbors and providing incentive health education about Lung TBC. Keywords: Lung Tuberculosis (TBC), Preventive Behavior